2015
DOI: 10.1590/0103-8478cr20140927
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens: a review of the disease in pigs, horses and broiler chickens

Abstract: Clostridium perfringens is a gram-positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…A clostridial ‘syndrome’ in suckling and weaner pigs, with risk factors of high injectable ceftiofur use and poor hygiene, presented an opportunity to engage in management change to improve pig health and cease/reduce ceftiofur use on four farms. Diagnosis of clostridial disease was greatly improved by use of a multiplex ELISA test.…”
Section: Methodsmentioning
confidence: 99%
“…A clostridial ‘syndrome’ in suckling and weaner pigs, with risk factors of high injectable ceftiofur use and poor hygiene, presented an opportunity to engage in management change to improve pig health and cease/reduce ceftiofur use on four farms. Diagnosis of clostridial disease was greatly improved by use of a multiplex ELISA test.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Upadhaya et al [ 6 ] reported that inclusion of 0.1% organic acid mixture (10% malic, 13% citric, and 17% fumaric acids) in the diet of growing and finishing pigs had decreased E. coli counts. C. perfringens is a gram-positive, anaerobic, and spore-forming bacillus that may produce major toxin microbiota in animals and humans [ 30 ]. Such toxic C. perfringens residents were significantly reduced in pigs fed FMP supplementation during both phases (d 21 and d42).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, spore-forming Clostridium strains are recognized as the primary cause of diarrhea in neonatal and weaned piglets [ 49 ]. Previous studies reported that the spores and toxins from C. difficile and C. perfringens originated during the lactation period induced high rates of diarrhea and mortality after weaning [ 49 , 50 , 51 ]. Moreover, Terrisporobacter produces the urinary toxin, such as trimethylamine- N -oxide, which is associated with oxidative stress and inflammation in the gut of weaned pigs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%